Research Progress in the Treatment of Knee Osteoarthritis Using Meridian Theory - Bai, Wentao; Dou, Qunli (Journal of Contemporary Medical Practice, 2025)
Knee osteoarthritis (KOA) is a kind of disease which is often characterized by knee pain, stiffness and muscle movement disorders, affecting the daily mental and physical health activities of arthritis patients and the quality of family life. Meridian ligament is one of the most important joint structure bases of human body to maintain hip joint activity and stability, and knee muscles will be rapidly and permanently damaged due to the damage of meridian ligament in the process of acute disease, therefore, the clinical research of Chinese medicine meridian ligament theory as a basic guide and based on the theory of clinical treatment of KOA has a considerable depth of the scope of medical research and therapeutic application of the value of practice. This paper systematically elaborates and discusses what is the basic theory of Chinese medicine meridians and tendons, the correspondence between meridians and tendons and western medicine KOA research, as well as the specific research of Chinese medicine meridian and tendon therapy theory in KOA practice, so that readers can better study the guidance and clinical treatment.